Panchromatic Type II Photoinitiator for Free Radical Polymerization Based on Thioxanthone Derivative - Tar, Haja; Esen, Duygu Sevinc; Aydin, Meral; Ley, Christian; Arsu, Nergis; Allonas, Xavier (AMER CHEMICAL SOC, 2013)
A new photoinitiator for free radical photopolymerization, belonging to the thioxanthone derivatives, was synthesized and characterized It was found that the compound absorbs over the whole UV-vis spectrum with relatively high absorption coefficients. Fluorescence studies reveal that three different singlet excited states are responsible for this absorption. Phosphorescence and laser flash photolysis evidence the formation of a triplet state from which a photoreduction can occur. Consequently, initiating radicals were formed which are able to initiate the photopolymerization of methyl methacrylate in DMF. Finally, the photopolymerization of acrylates was performed in film at different wavelengths such as 392, 476, 532, and 632 nm, emphasizing the possibility to use this novel photoinitiator when panchromatic irradiation is required.
Keywords: OXYGEN INHIBITION; PHOTOPOLYMERIZATION; SOLVENT; SYSTEMS; PHOTOCHEMISTRY; DEPENDENCE; STATES; Polymer Science